Nuclear Reactors Spacecraft Propulsion, Research Reactors, and Reactor Analysis Topics - Pope, Chad L. (IntechOpen, 2022)
Worldwide interest in nuclear reactors continues to increase and significant focus has been placed on advanced nuclear reactors intended to produce electricity and process heat. However, there is limited literature on the importance of research reactors and certain specialized reactor analysis topics. Thus, this book addresses these topics over three sections: "Nuclear Reactors for Spacecraft Propulsion", "Research Reactors", and "Select Reactor Analysis Techniques". It provides detailed information on the use of nuclear reactors for spacecraft propulsion, presents research conducted on reactors in Idaho, USA, and discusses reactor analysis topics such as cyber-informed engineering for nuclear reactor digital instrumentation and control, the effect of plenum gas on fuel temperature, and more.